The Impact of the Internet Adoption on the Information Search for High and Low Involvement Products: An Empirical Study Based in Taiwan - Wang, Ting (2006)
The dissertation aims at unravelling the implicit antecedents and consequences of consumer information searching activities in an online context. The involvement theory has been incorporated which concentrates on the mental aspect of consumers' behaviour as a complement to the traditional consumer decision making model. Cosmetics and toothpastes are chosen as the representative product categories for high and low product involvement respectively. Previous researchers have suggested that the amount and pattern of consumers' online information searching activities are influenced by the level of product involvement to a great extent. Thus, it is reasonable to integrate the concept into the study of online consumer information search.